Optimizing drug discovery for snakebite envenoming via a high-throughput phospholipase A2 screening platform - Albulescu, Laura-Oana; Westhorpe, Adam; Clare, Rachel H.; Woodley, Christopher M.; James, Nivya; Kool, Jeroen; Berry, Neil G.; O’Neill, Paul M.; Casewell, Nicholas R. (Frontiers in Pharmacology, 2024)
Snakebite envenoming is a neglected tropical disease that causes as many as 1.8 million envenomings and 140,000 deaths annually. To address treatment limitations that exist with current antivenoms, the search for small molecule drug-based inhibitors that can be administered as early interventions has recently gained traction. Snake venoms are complex mixtures of proteins, peptides and small molecules and their composition varies substantially between and within snake species. The phospholipases A2 (PLA2) are one of the main pathogenic toxin classes found in medically important viper and elapid snake venoms, yet varespladib, a drug originally developed for the treatment of acute coronary syndrome, remains the only PLA2 inhibitor shown to effectively neutralise venom toxicity in vitro and in vivo, resulting in an extremely limited drug portfolio. Here, we describe a high-throughput drug screen to identify novel PLA2 inhibitors for repurposing as snakebite treatments. We present method optimisation of a 384-well plate, colorimetric, high-throughput screening assay that allowed for a throughput of ~2,800 drugs per day, and report on the screening of a ~3,500 post-phase 1 repurposed drug library against the venom of the Russell's viper, Daboia russelii. We further explore the broad-spectrum inhibitory potential and efficacy of the resulting top hits against a range of medically important snake venoms and demonstrate the utility of our method in determining drug EC50s. Collectively, our findings support the future application of this method to fully explore the chemical space to discover novel PLA2inhibiting drugs of value for preventing severe pathology caused by snakebite envenoming.